2021
DOI: 10.1007/s10120-021-01204-6
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of four prediction models for risk stratification in gastric cancer screening among a high-risk population in China

Abstract: Objective Early detection of gastric cancer (GC) is a critical step for decreasing mortality. The aim of this study was to evaluate the performance of four prediction models for risk stratification in the screening of GC and precancerous lesions among a large, high-risk population in China. Design This study was a retrospective analysis of data from the Provincial Gastric Cancer Screening Program (Zhejiang, China) spanning the period between October 2016 and April 2019, in which 97,541 individuals from the urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
(40 reference statements)
2
10
0
Order By: Relevance
“…6 risk factors were identified and included based on statistical analysis in this study: patient gender, lesion size, location, border line, number, and erosion. A national multicenter study 13 , 14 showed that gender was an independent risk factor for high-risk gastric cancer, with OR 2.52 (1.92 to 3.30), P < .001, which was consistent with our results. However, our results indicated that there was no significant correlation between gastric LGIN progression and age.…”
Section: Discussionsupporting
confidence: 92%
“…6 risk factors were identified and included based on statistical analysis in this study: patient gender, lesion size, location, border line, number, and erosion. A national multicenter study 13 , 14 showed that gender was an independent risk factor for high-risk gastric cancer, with OR 2.52 (1.92 to 3.30), P < .001, which was consistent with our results. However, our results indicated that there was no significant correlation between gastric LGIN progression and age.…”
Section: Discussionsupporting
confidence: 92%
“…This nationwide study successfully developed and validated prediction rule identifying individuals at a higher risk in a Chinese high-risk population, which needed to receive further gastroscopy. Compared to ABC method ( Miki, 2011 ), five markers-based method ( Tu et al., 2017 ), the prediction model of seven variables ( Cai et al., 2019 ) showed higher Area Under the Curve and Youden index values, which was further confirmed by a retrospective analysis of data from the Provincial Gastric Cancer Screening Program with 97, 541 individuals included ( Hu et al., 2021 ). A future large population-based screening project should be launched to test and validate its efficacy of novel GC risk prediction rule.…”
Section: The Stratification Of Risk For Gc In the Chinese Gc Risk Pop...mentioning
confidence: 72%
“…However, several population‐based studies have shown significant country‐specific differences in the proportions of ABCD groups according to the ABC method between Japan and China 11–19 . Compared with Japan, a larger proportion of individuals were classified as Group B (Hp [+] and PG [−]) in China.…”
Section: Introductionmentioning
confidence: 99%
“…10 However, several population-based studies have shown significant country-specific differences in the proportions of ABCD groups according to the ABC method between Japan and China. [11][12][13][14][15][16][17][18][19] Compared with Japan, a larger proportion of individuals were classified as Group B (Hp [+] and PG [−]) in China. Therefore, screening gastroscopy cannot be offered to all participants in Group B due to the high costs in China.…”
mentioning
confidence: 99%